Aerodynamic drag modeling of alpine skiers performing giant slalom turns - Meyer, F.; Le Pelley, D.; Borani, F. (Medicine & Science in Sports & Exercise, 2012)
Purpose: Aerodynamic drag plays an important role in performance for athletes practicing sports that involve high-velocity motions. In giant slalom, the skier is continuously changing his/her body posture, and this affects the energy dissipated in aerodynamic drag. It is therefore important to quantify this energy to understand the dynamic behavior of the skier. The aims of this study were to model the aerodynamic drag of alpine skiers in giant slalom simulated conditions and to apply these models in a field experiment to estimate energy dissipated through aerodynamic drag.